The Strategic Role of School Supervisors in Strengthening Educational Supervision and Teacher Development - Aldiani, Irma; Asmendri, Asmendri (Journal of Social Studies Arts and Humanities (JSSAH), 2025)
This study aims to examine strategies for strengthening the professional roles and competencies of school supervisors in managing and improving the quality of education. School supervisors play a vital role as professional educators who are responsible for implementing academic and managerial supervision in schools. Their responsibilities include planning, monitoring, evaluating, and guiding teachers and principals to achieve educational effectiveness. Using a literature review approach, this research synthesizes previous studies and regulations related to the professional scope, duties, and competencies of school supervisors. The findings indicate that supervisors serve as facilitators, consultants, and evaluators who support teachers’ professional growth and institutional performance improvement. However, several challenges remain, such as limited supervisory skills, inconsistent implementation of supervision programs, and the need for continuous professional development. Therefore, strengthening the competence of school supervisors should be conducted through structured training programs and collaborative professional forums such as the Kelompok Kerja Pengawas Sekolah (KKPS) and Musyawarah Kerja Pengawas Sekolah (MKPS). These platforms promote knowledge sharing, reflective practice, and collective learning, ultimately enhancing the effectiveness of educational supervision and school management.